Growing Up in Wales: An hybrid electronic and traditional cohort using administrative, health and survey data. - James, Michaela; Jones, Hope (International Journal of Population Data Science, 2025)
Objectives The Growing up in Wales Cohort brings together a birth cohort (Born in Wales) and a primary school cohort (HAPPEN) to create a national children’s cohort. GUIW brings together education, health and survey data to enable life course research and the evaluation of national interventions and policy in practice. Method The cohort includes Born in Wales; the linked electronic data on 400,000 births combined with survey responses from 4000 parents. The electronic cohort comprises all children born in Wales since 2011, with follow-up conducted until they finish primary school at age 11. BiW will expand by 30,000 births annually in Wales with linkage to household data enabling follow-up of children, their siblings and parents. Additionally, the HAPPEN cohort includes children in primary schools in Wales linked with self-report survey of over 45,000 primary-aged school children from 2016 to 2024. The survey continues to rise by 7000–8000 responses annually. Results GUIW has shown trends in declining mental and physical wellbeing in 7-11 year olds, underscoring the need for early intervention. It has also revealed key risk factors for low birth weight, disparities in breastfeeding rates, and barriers to school readiness. Current research includes evaluation of natural experiments including those to address poverty such as; the free school meal roll-out in Wales and healthy weight, built environment of schools and respiratory health, maternity grants and birth outcomes, and health visitor assessments and their impact on child health and attainment. Additionally, the importance of father involvement in family health research was emphasised, addressing barriers to participation. Findings inform future policy and practice, advocating for inclusive, data-driven approaches to improving child outcomes across Wales. Conclusion This is a unique national children’s cohort which include electronic linked data on members of the household, self-assessed health by children themselves and the ability to evaluate policy and practice. PPI is integral to its growth ensuring that the public actively participate in shaping research priorities.